STRATEGI ORANG TUA TERHADAP PENDIDIKAN SEKS UNTUK ANAK USIA 5-6 TAHUN DI RAUDHATUL ATHFAL RAHMAH EL YUNUSIYYAH PADANG PANJANG - Andriani, Yuli; Kardi, Juliwis; Lestari, Mega Cahaya Dwi (PSGA LP2M IAIN Pontianak, 2024)
Sex education for children is education to introduce private and closed parts of the body that must be maintained. This research began with the problem that researchers found at RA Rahmah El-Yunusiyyah Padang Panjang that many children's questions were related to sexuality. The purpose of this sex education is to understand sexual behaviors that appear according to the child's age. This sex education is also expected to minimize things that parents do not want related to the many cases of sexual violence that occur against early childhood.This study aims to describe and find out parents' strategies for sex education for 5-6 year old children in Raudhatul Athfal Rahmah El-Yunusiyyah Padang Panjang. This type of research is a qualitative and using approach and naturalistic phenomenology. The data collection method in this study uses observation, interviews, and documentation. Furthermore, to test the validity of the data, the researcher uses the triangulation technique. Then to analyze the data, the researcher divided it into three components, including: data reduction, data display (data presentation) and conclusion drawing (data verification).Based on the results of the interviews conducted by the researcher, it can be concluded that parents do not know sex education for 5-6 year old children in RA REY, therefore of the 8 (eight) strategies written in the parental theory have not been maximized in applying to children, because parents are constrained by the lack of sex science for children so that parents often run away from questions and are not open in delivering sex education to children. Although parents know the great benefits for their children in the future so that they can keep their children away from sexual deviations in adolescence, parents have not yet provided sex education according to the child's age stages.Keywords: Parent Strategy, Sex Education